A Step Toward a New International Arbitration Hub or Merely a Procedural Reform? the Implications of Supreme Court Regulation No. 3 of 2023 on Arbitration in Indonesia - Rifcky Amarthtya Ardiatama Utomo (Journal of Social Research, 2026)
As business transactions become increasingly complex in the era of globalization, the need for effective, efficient, and responsive dispute resolution mechanisms has become more urgent. Arbitration, as a non-litigation alternative, offers key advantages such as procedural flexibility, confidentiality, and greater efficiency in time and cost compared to conventional litigation. In Indonesia, arbitration is primarily governed by Law Number 30 of 1999; however, the rapid evolution of global arbitration practices highlights the necessity for more adaptive regulatory reforms. The issuance of Supreme Court Regulation Number 3 of 2023 (PERMA 3/2023) represents a progressive effort to strengthen the procedural framework of arbitration, particularly in relation to arbitrator appointment, default mechanisms, enforcement and annulment of awards, and the digitalization of judicial administration. This study aims to analyze the contribution of PERMA 3/2023 in improving the effectiveness of arbitration in Indonesia and identify the normative and practical limitations that are still faced. The method used is a normative juridical approach with an analysis of laws and regulations and arbitration practices. The results of the study show that PERMA 3/2023 has succeeded in increasing procedural certainty and efficiency in the interaction between arbitration and the judiciary. However, there are still a number of problems, including inconsistencies in the regime for the recognition of international arbitral awards, ambiguity in the application of arbitrator immunity, and limitations in the arrangement of interlocutory awards. Therefore, further reforms are needed at the legislative level to realize a competitive arbitration system that is in line with international standards